PERANCANGAN APLIKASI SUPPLY CHAIN MANAGEMENT PADA DISTRIBUSI AYAM POTONG PT. NUJ / MTS DENGAN MENGGUNAKAN METODE DISTRIBUTOR REQUIRMENT PLANNING (DRP) - Dinul Akhiar (Sekolah Tinggi Teknologi Industri Padang, 2016)
A company will be faced with problems relating to the distribution system. Thisproblem arises because consumers are in geographically dispersed locations, this resulted in the importance of holding inventories at several location. PT.Nuj / Mts is the distribution company, this company manufactures the product. PT.Nuj / Mts not yet have a good distribution planning. Planning distribution company run by less effective and has few weaknesses. Given these problems, then conducted research with the method of Distribution Requirements Planning (DRP) in the hope to be distributing the product from factory to each of city in an optimal distribution. Distribution Requirements Planning is a method to handle the procurement of supplies in a multi-echelon distribution network. The purpose of the Distribution Requirements Planning (DRP), which make a planning and scheduling activities of a good distribution, so that success in meeting customer demand will be more optimal, increase performance in fulfilling orders in a timely and appropriate amount so that distribution costs can be reduced minimized. Ofthe results, themethod ofdistribution planningcompany, the Total Cost of distribution including product demand data, product price, booking fees, storage fees, shipping costs and lead time data. By using DRP method, in order be expected to more profitable company in the future. Keywords:Distribution, Distribution Requirements Planning (DRP)